THE EFFECT OF USING THE JIGSAW LEARNING MODEL ON THE INDONESIAN LANGUAGE LEARNING OUTCOMES OF GRADE V STUDENTS OF PRIVATE ELEMENTARY SCHOOL MASEHI NO. 3 KABANJAHE - Sinuraya, Fitri Rohayati Br; Ginting, Nurlia; Yunistita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Effective education is greatly influenced by the learning methods used. In elementary schools, conventional learning methods are often unable to optimally improve student learning outcomes, especially in Indonesian language subjects. Therefore, an innovative approach is needed to improve student understanding of the material being taught. One method considered effective is the Jigsaw learning model, which encourages active collaboration among students. This study aims to determine the effect of the Jigsaw learning model on Indonesian language learning outcomes for fifth-grade students at SD Swasta Masehi No. 3 Kabanjahe, focusing on poetry and pantun materials. This study uses a quantitative, experimental design. The research sample consisted of two groups: the experimental group, which received treatment using the Jigsaw learning model, and the control group, which used conventional learning. Data were collected through pretest and posttest measures, which were analyzed using the Paired-Samples t-Test. The results showed that the experimental group experienced a significant increase in learning outcomes. The average posttest score for the experimental group was 87.55, while the control group reached only 74.05. The results of the hypothesis test showed a t-value of 6.107 and a p-value of 0.000, which is less than 0.05; thus, the alternative hypothesis is accepted, and the null hypothesis is rejected. The application of the Jigsaw learning model significantly improves students' Indonesian language learning outcomes, especially in poetry and pantun materials. This learning model can be implemented as an innovative alternative to improve the quality of learning in elementary schools.